Age Differences in the Associations Between Outness and Suicidality Among LGBTQ+ Youth. Issue 2 (3rd April 2023) - Feinstein, Brian A.; Mereish, Ethan H.; Mamey, Mary Rose; Chang, Cindy J.; Goldbach, Jeremy T.
Abstract: Objective: Lesbian, gay, bisexual, transgender, and queer (LGBTQ+) youth are at increased risk for suicidality compared to their heterosexual and cisgender peers, and outness (the extent to which an individual is open about their LGBTQ+ identity to others) is an important correlate of suicidality. However, previous research has led to mixed findings regarding whether outness functions as a risk or protective factor for suicidality, and the available evidence suggests that age may play an important role. As such, the goal of the current study was to examine whether the associations between outness and suicidality differed between LGBTQ+ adolescents (ages 12–17) and emerging adults (ages 18–24). Method: The analytic sample included 475 LGBTQ+ youth who completed an online survey after contacting a national, LGBTQ+ crisis service provider. Results: Results indicated that age significantly moderated the association between outness and suicidal ideation, such that greater outness was significantly associated with greater suicidal ideation for adolescents, but not for emerging adults. In contrast, age did not significantly moderate the associations between outness and likelihood of a past suicide attempt or perceived likelihood of a future suicide attempt. However, the main effect of outness was significant in both models, such that greater outness was significantly associated with a greater likelihood of a past suicide attempt and a greater perceived likelihood of a future suicide attempt. Conclusions: These findings suggest that the associations between outness and suicidality among LGBTQ+ youth may depend on age as well as the dimension of suicidality (ideation versus attempt). Highlights: Being more open about one's LGBTQ+ identity may confer risk for suicidality. The influence of outness on suicidal ideation may be strongest during adolescence. There is a need for LGBTQ+ affirming policies and laws to reduce suicidality.